Characterizing Demographic and Geographical Differences in Health Beliefs and Dietary Habits Related to Colon Cancer Risk in US Adults - Schaberg, Megan N.; Smith, Kristen S.; Greene, Michael W.; Frugé, Andrew D. (Frontiers in Nutrition, 2020)
Background: Colon cancer (CC) risk is increased by behavioral factors including a diet high in red meat (RM) and processed meat; excess adiposity has contributed to a rise in CC in younger adults. The willingness of at-risk adults to modify behaviors to reduce CC risk warrants further investigation. Methods: The previously validated Dietary Habits and Colon Cancer Beliefs Survey (DHCCBS) was used to assess attitudes and beliefs related to CC risk and diet behavior. An abbreviated food frequency questionnaire was included in the survey to quantify RM and green leafy vegetable (GLV) intake over the previous 30 days. Independent samples t-tests compared RM and GLV intake and DHCCBS responses. One-way analysis of variance with post-hoc LSD correction was completed to assess these differences within three age groups (<35, 35-44, and 45-54 years old) and between U.S. Census Bureau geographical regions. Results: 838 survey responses were analyzed. Perceived severity of CC diagnosis was significantly lower in younger adults (<35) compared to older adults (35-44, p=0.042; 45-54, p=0.003). Furthermore, younger adults (<35) perceived fewer barriers (i.e. taste preference) to GLV consumption than their older adult counterparts (35-44, p=0.019; 45-54, p=0.002). Few regional differences in habitual RM consumption were observed, however, several disparities were observed with GLV. Conclusion: These findings from the DHCCBS indicate health beliefs towards CC risk are influenced by an individual’s age and dietary habits. Additionally, regional differences in GLV consumption indicate opportunities for risk-reduction-focused health messages, particularly in the southern United States where CC incidence and mortality are highest.